ROLE OF ALCOHOLIC TURMERIC (CURCUMA LONGA) EXTRACT IN OUTCOME OF IN VITRO SPERM ACTIVATION FOR INFERTILE PATIENTS (Iraqi Journal of Medical Sciences, 2016)
Background:Semen samples are prepared for assisted reproduction by selecting a population of highly motile, morphologically normal sperm and removing the seminal plasma, leukocytes and bacteria. Culture media provide the spermatozoa with needs that maintain optimal function of spermatozoa to give rise excellent results during semen preparation.Objective:The aim of this study was to investigate the effect of alcoholic extraction of turmeric (AET) on sperm parameters during in vitro sperm activation (ISA) for asthenozoospermic (AZ) and oligoasthenozoospermic (OAZ) patients.Methods: Seventy four infertile patients were included, and classified into two groups according to their sperm parameters. Semen sample was divided into 3 aliquots. One mL of Earl's medium either alone (control group) or supplied with one concentration of AET (5 µg/mL or 10 µg/mL) was over layered the pellet, and the three tubes were incubated at 37 oC for 30 min in air incubator. Sperm concentration, motility, grades activity, progressive motility, normal morphology and agglutination were assessed pre- and post-activation in vitro.Results:Results revealed an enhancement of most sperm parameters for control and both treated groups post-activation as compared to pre-activation. Post-ISA, sperm parameters for both treated groups were better than the control group. However, best results for improvement of sperm parameters were assessed within treated group (5 µg/mL of AET).Conclusions:The lower concentration of alcoholic turmeric extraction enhanced human sperm parameters during ISA without any harmful effects on sperm physiology. The results are also useful as a guide for further standardization of turmeric extracts used for pharmaceutical purposes in the techniques of assisted reproduction.Key words: Male infertility, Sperm activation, Turmeric.
Keywords: Male infertility; Sperm activation; Turmeric